The rise of BioBlitz: Evaluating a popular event format for public engagement and wildlife recording in the United Kingdom. Issue 4 (2nd October 2018) - Postles, Matthew; Bartlett, Madeleine
ABSTRACT: "BioBlitz" events are popular local wildlife surveys often engaging public audiences in a race against time to find, identify, and record as many different species as possible in a given timeframe. This study provides baseline assessment of the value of BioBlitz as a tool for public engagement and collection of environmental data in the United Kingdom. We conclude that, collectively, BioBlitz events provide participants with an enjoyable learning experience, engage new audiences in biodiversity issues, and inspire positive action. Challenges of verification and consolidation of BioBlitz records make the value of these data to the wider environmental sector difficult to quantify.